Memory Impairment in Relapsing-Remitting Multiple Sclerosis Using a Challenging Semantic Interference Task - Matias-Guiu, Jordi A.; Cortés-Martínez, Ana; Curiel, Rosie E.; Delgado-Álvarez, Alfonso; Fernández-Oliveira, Aníbal; Pytel, Vanesa; Montero, Paloma; Moreno-Ramos, Teresa; Loewenstein, David A.; Matías-Guiu, Jorge (Frontiers in Neurology, 2020)
Objective: Episodic memory is frequently impaired in Multiple Sclerosis (MS), but the cognitive characteristics and neuropsychological processes involved remain controversial. Our aim was to study episodic memory dysfunction in MS, using the LASSI-L, a novel memory-based cognitive stress test that uses a new paradigm that capitalizes on semantic interference. Methods: Cross-sectional study in which 93 patients with MS (relapsing-remitting) and 124 healthy controls were included. The LASSI-L test was administered to all participants, as well as a comprehensive neuropsychological battery including a selective reminding test. MS patients were divided into two groups, with cognitive impairment (CI-MS) and cognitively preserved (CP-MS). Results: Reliability of the LASSI-L test was high (Cronbach’s alpha 0.892) and there were less ceiling effects. MS patients scored lower than controls on all LASSI-L subtests, except for maximum storage of the initial target items (CRA2). Effect sizes were moderate-large. A delay in learning, difficulties in retroactive semantic interference, failure to recover from proactive semantic interference, and delayed recall were the most frequent findings in MS patients. Scores associated with maximum storage capacity, and retroactive semantic interference were the most strongly associated with cognitive impairment and employment status. Conclusion: We found that deficits in maximimum learning, difficulties in recovery from the effects of proactive semantic interference and retroactive semantic interference are three important breakdowns in episodic memory deficits among patients with MS. The LASSI-L showed good psychometric and diagnostic properties. Overall, our study supports the utility of the LASSI-L, as a new cognitive test, useful for neuropsychological assessment in MS in clinical and research settings.